2019
DOI: 10.1128/jvi.00711-19
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Barriers Limit Reversion of a Proofreading-Deficient Coronavirus

Abstract: The 3=-to-5= exoribonuclease in coronavirus (CoV) nonstructural protein 14 (nsp14-ExoN) mediates RNA proofreading during genome replication. ExoN catalytic residues are arranged in three motifs: I (DE), II (E), and III (D). Alanine replacement of the motif I residues (AA-E-D; four nucleotide substitutions) in murine hepatitis virus (MHV) and severe acute respiratory syndrome (SARS)-CoV yields viable mutants with impaired replication and fitness, increased mutation rates, and attenuated virulence in vivo. Despi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…As reported for MHV and SARS-CoV ExoN mutants ( 23 , 78 ), possible (late) reversion was observed for a few of our MERS-CoV ExoN active-site mutants, specifically, those with E191A, D273E, D273A, and in particular D90E, which had reverted by 6 dpt in four of eight experiments. Together with the immunolabeling results presented in Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As reported for MHV and SARS-CoV ExoN mutants ( 23 , 78 ), possible (late) reversion was observed for a few of our MERS-CoV ExoN active-site mutants, specifically, those with E191A, D273E, D273A, and in particular D90E, which had reverted by 6 dpt in four of eight experiments. Together with the immunolabeling results presented in Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Although the E191D mutant was somewhat more sensitive to the mutagenic agent 5-FU ( Fig. 5C and D ) ( 28 , 78 ), its ExoN activity does not appear to be dramatically altered by this conservative substitution in the active site.…”
Section: Discussionmentioning
confidence: 93%
“…The finding that MHV-ExoN(-) has decreased recombination during viral replication may have important implications for any design of live-attenuated SARS-CoV-2 or other animal or zoonotic CoVs. Our previous studies have shown that the ExoN(-) substitutions in MHV and SARS-CoV are evolutionarily stable over long-term passage in culture and in mice, and that a SARS-CoV ExoN(-) mutant is attenuated in mice while producing a robust and protective immune response against WT SARS-CoV infection [ 38 , 42 , 58 , 59 ]. The results in this paper raise the intriguing possibility that any CoV encoding ExoN(-) would have less recombination potential for repair or escape.…”
Section: Discussionmentioning
confidence: 99%
“…In another program, rescue of viable ExoN(-) human CoV 229E (HCoV-229E) was unsuccessful, but limited replication was associated with decreased detection of sgmRNAs [34,41]. Although these reports did not study recombination or molecular mechanisms, they support the hypothesis that CoV nsp14-ExoN activity RNA synthesis and possibly recombination, in addition to the known functions of nsp14-ExoN in CoV replication fidelity, viral fitness, in vivo virulence, resistance to nucleoside analogues, and immune antagonism [36,42,43].…”
Section: Plos Pathogensmentioning
confidence: 97%
“…2017, Graepel et al. 2019). Remarkably, however, the compensatory mutations are never back mutations at the altered proofreading positions, nor anywhere else in the proofreading domain.…”
Section: A Consideration Of Viral Mutation Ratesmentioning
confidence: 99%